The fundamentals of product design - Morris, Richard, 1962- (AVA academia., 2009)
Product Design can be a challenging field of study because the discipline touches on so many subject areas such as materials, manufacturing, idea generation, CAD, engineering functions, art, market research and product types. By exploring a variety of key areas, The Fundamentals of Product Design provides an integrated and cohesive view of the product design process and offers pointers about what factors to consider and where your next steps might take you at each stage of the process. The Fundamentals of Product Design can be used as both a reference text and useful guide. Each chapter is packed with examples of work from talented designers around the globe, which help illustrate points in the text and will fuel and inspire your own creativity. -- From the Back Cover.